The Relationship Between The Characteristics Of School-Age Children And The Incidence Of Bullying At SDN 31 Bontoraja - Haerani; Nuraksanita; Fitriani (Jurnal Life Birth, 2021)
The incidence of bullying in schools is not something new anymore. However, until now the incident of bullying has not been handled specifically. While it is known that bullying is a trigger for acts of violence against children. Violence is one form of action in the form of physical force, threats, or certain associations with the intention to hurt and cause physical or mental injury. Bullying is defined as suppression that is carried out intentionally, aggressively, which is carried out strongly by an individual or group. There are several factors that can influence the incidence of bullying in children, including the characteristics of the child itself. The purpose of this study was to determine the relationship between the characteristics of children and the incidence of bullying at SDN 31 Bontoraja. This research method uses an analytical observational design with a Cross Sectional approach . With a total sample population of 71 and the number of samples as many as 41 people. This research uses a sampling technique, namely probability sampling using a simple random sampling technique, also called simple. In this study, the results showed that for a low level of bullying as many as 19 people and a high level of bullying as many as 22 people. And the results of the bivariate analysis using the chi-square test obtained results for the three independent variables, namely the level of age, gender, and family environment that H0 was accepted. In this study, it can be concluded that the characteristics of school-age children consisting of age, gender, and family environment have no relationship with the incidence of bullying. Parents always control their children in socializing, using electronic and print media, for example, parents taking their children to school, accompanying their children to watch television.